Gereformeerde pietisme, neoplatonisme en pre-Romantieke teodisee in die Voortrekkervrou Susanna Smit (1799-1863) se godsdienstige dagboeke - Raath, A. W. G. (Koers, 2023)
Reformed Pietism, neo-Platonism and pre-Romantic Theodicy in the spiritual diaries of the Voortrekker woman Susanna Smit (1799-1863 The first half of the eighteenth century witnessed a resurgence of Platonism in literature generally and in theology in Germany en Holland in particular, because of the appeal Plato’s ideas held for the distinction between immanent and transcendental reality, man’s quest for unity with the Good, and the human soul as the vehicle for uniting with God. Because most human beings are preoccupied with material things, Plato believed they need to have their thoughts turned to the immaterial reality behind the material world, and thus to be weaned away from the objects of their passions. To Plato the world is more than a world of appearances. Behind each particular thing is the idea or form of the thing. Moreover, the ideas or forms are all ultimately related to the Form of the Good. Plato believed that the soul is an immaterial entity, which in some ways is like the Forms. Particularly revealing to the emerging trend of Romanticism was Plato’s philosophical transcending of sceptical and materialistic views of reality, the notion that those who know what is good will love and desire it, and that moral virtue is of itself a prerequisite to knowing the good. The problem presented itself as to how sinful man and chaos in the world can be brought in accordance with God’s perfect and sinless nature. Because Plato’s view of human improvement by means of education and salvation through personal virtue is far removed from the Christian message of redemption by a loving, personal God, Pietists reverted to the neo-Platonism legacy of love mysticism to resolve the dualism inherent to the Romantic juxtaposition of the immanent and the transcendent. The Voortrekker woman Susanna Smit reflected these influences in her Reformed Pietistic spirituality and re-interpreted the Christian conviction of the love of God and man’s salvation by relying on neo-Platonism love spirituality in the works of James Hervey, Rutger Schutte, Hieronymus van Alphen, Rhijnvis Feith and other pietistically inclined authors. This research investigates the impact of the idea of experiential numinous love mediating between the Good and the human soul and neo-Platonism love sentimentality in Susanna Smit’s diaries and the effect of these influences in her Reformed Pietistic spirituality from 1843 to 1863.